Solvents and properties polymer solutions for electrospinning. - M. Y. Nebratenko; Y. A. Naumova; Y. N. Filatov (Тонкие химические технологии, 2008)
The given article represents the bases of selection of solvents for polymer solutions. The results of the research indicate that the solvent is an effective instrument which allows the combination of polymers through the solutions. These solutions are employed for creating fibrous materials.